2018
DOI: 10.1093/cvr/cvy055
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by cardiac progenitor cell-secreted exosomes: role of pregnancy-associated plasma protein-A

Abstract: These results suggest that CPC-secreted exosomes may be more cardioprotective than BMC-secreted exosomes, and that PAPP-A-mediated IGF-1 release may explain the benefit. They illustrate a general mechanism whereby exosomes may function via an active protease on their surface, which releases a ligand in proximity to the transmembrane receptor bound by the ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
181
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(192 citation statements)
references
References 32 publications
9
181
1
1
Order By: Relevance
“…Bian et al29 found the same results when they treated the rats with AMI with exosome extracted from human BMSCs. Through a comparison of cardiac‐resident progenitor cell–secreted exosomes and BMSC‐secreted exosomes, Barile et al30 explained that the cardioprotection of exosomes may act via the pregnancy‐associated plasma protein‐A mediated insulin‐like growth factor‐1 release and subsequently modulate intracellular protein kinase B and extracellular signal regulated kinase 1/2 phosphorylation. Feng et al31 demonstrated that exosomes released from ischemic preconditioned MSCs contained an increased amount of miR‐22, which could exert a silence effect on methyl CpG binding protein 2 to ameliorate apoptosis in mice with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Bian et al29 found the same results when they treated the rats with AMI with exosome extracted from human BMSCs. Through a comparison of cardiac‐resident progenitor cell–secreted exosomes and BMSC‐secreted exosomes, Barile et al30 explained that the cardioprotection of exosomes may act via the pregnancy‐associated plasma protein‐A mediated insulin‐like growth factor‐1 release and subsequently modulate intracellular protein kinase B and extracellular signal regulated kinase 1/2 phosphorylation. Feng et al31 demonstrated that exosomes released from ischemic preconditioned MSCs contained an increased amount of miR‐22, which could exert a silence effect on methyl CpG binding protein 2 to ameliorate apoptosis in mice with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NT5E (CD73) and ENG (CD105), two of the minimally required cell surface antigens for MSC were detected in seven out of ten, and THY1 (CD90), in eight out of ten datasets (Table ). Please note that some datasets contain relatively low amounts of reported IDs (<500), which can be explained by that fact that one datasets only reports quantified IDs, and that for two other studies, the proteomics approach was limited to identifying only the relatively more abundant proteins …”
Section: Resultsmentioning
confidence: 99%
“…Independent landmark studies reported that exosomes released by human CPCs or human cardiosphere‐derived cells (CDCs) inhibit apoptosis and promote the proliferation of cardiomyocytes, while enhancing angiogenesis. Exosomes from both CDCs and CPCs reduce scar size and improve ventricular function in rodent MI models, the latter being more cardioprotective than bone marrow‐MSC exosomes derived from the same patients, when compared with dermal fibroblast exosomes . Cardioprotective effects are also induced ‘in vitro’ and ‘in vivo’ by cardiac fibroblast exosomes, while those released from human normal dermal fibroblasts do not exert these beneficial effects .…”
Section: Cell‐free Cardiac Regenerationmentioning
confidence: 99%
“…Exosomes from both CDCs and CPCs reduce scar size and improve ventricular function in rodent MI models, 38,39 the latter being more cardioprotective than bone marrow-MSC exosomes derived from the same patients, when compared with dermal fibroblast exosomes. 40 Cardioprotective effects are also induced 'in vitro' and 'in vivo' by cardiac fibroblast exosomes, 41 while those released from human normal dermal fibroblasts do not exert these beneficial effects. 38,40 Finally, BMC and CPCs exosomes increase blood vessel density in the infarct region.…”
Section: Cell-free C Ard Iac Reg Ener Ati Onmentioning
confidence: 99%